Anti-Ro52 antibody is an independent risk factor for interstitial lung disease in dermatomyositis. (October 2020) - Xing, Xiaojing; Li, Anqi; Li, Chengxin
Abstract: Aim: Recent studies have shown that anti -Ro52 antibody is associated with both interstitial lung disease (ILD) and the degree of disease severity in juvenile patients with dermatomyositis (DM). We found that more than half of adult patients with DM were positive for anti -Ro52 antibody. In this study, we analysed the correlation between anti -Ro52 antibody and ILD in adult patients with DM. Method: Serum samples were collected from 153 adult inpatients with DM, at the First Medical Centre of PLA General Hospital, Beijing, China, who met the classification criteria of idiopathic inflammatory myopathies from March 1, 2016 to September 30, 2019. The patients were followed up to May 31, 2020. Immunoblotting was used to detect 16 types of myositis-specific autoantibodies (MSAs) and myositis-associated autoantibodies (MAAs) from serum samples. High-resolution computed tomography (HRCT) was used to calculate the ILD score, and tumours were screened. Clinical data and HRCT scores were evaluated and analysed retrospectively. Results: Our results showed that anti -Ro52 antibodies were the most commonly found antibodies in patients with DM, with a positive rate of 52.9%. Anti -Ro52, anti -aminoacyl-tRNA synthetase (anti-ARS), and anti-melanoma differentiation-related gene 5 ( anti -MDA5) antibodies were found to be risk factors for ILD development. Anti -Ro52 antibodies had a strong predictive effect on ILD in patients with DM. Conclusion: The occurrence of ILD is highly likely in patients with DM who are positive for the anti -Ro52 antibodies. Thus, anti -Ro52 antibodies is an independent risk factor for ILD in patients with DM. Highlights: Anti-Ro52 antibodies were the most commonly found antibodies and an independent risk factor for ILD in patients with DM. Anti-Ro52, anti-ARS and anti-MDA5 antibodies were found to be risk factors for ILD development in DM. Anti -Ro52 antibodies had a predictive effect on ILD development and are an independent risk factor for ILD in patients with DM. When both anti -Ro52 and anti -MDA5 antibodies were present, the HRCT scores of ILD increased.